(untitled) (Eastern Librarian, 2012)
This paper reports the results of the citation analysis of The Journal of Poultry Science (JPS). The major objectives of the study from the year 2001 to 2010 are to find out the authorship and citation patterns of articles appeared in the JPS. The total 425 articles were published during the period. Overall 13012 citations featuring 425 contributors have been made. Among the citations, journal articles accounted for 84%, books 8% and anothers 8%. The ratio of Author Self Citation to total citations is 1:16. The ratio of Journal Self Citation to total citations 1:58. It is also clear that majority of the documents 10102 (78%) cited in these issues were published not more than 20 years ago. DOI: http://dx.doi.org/10.3329/el.v23i1.12121 Eastern Librarian Vol.23(1) 2012 pp.64-73